IKLAN KOMERSIAL MEDIA CETAK: TINJAUAN TEKS DAN KONTEKS - Moh. Masrukhi (Arabic Literature Department, 2016)
Advertising is the means the company to introduce, promote products, and sell them to the public. Print ads generally use verbal element of the display (text) and nonverbal elements (contexts). These two elements with sales messages conveyed to the reader or potential consumers. Therefore, the problem is how to link these elements to form a whole discourse in commercial advertising (IKOMES), especially in the print media in Egypt. What is the structure of these elements and how the meaning or message(s) contained in it, and how the meaning or message that contained therein. So, thereader can understand what the advertiser wishes. A number of research data is collected from various newspapers and magazines that published in Egyptwhich containelements of verbal and nonverbal as well as having elements as Leech concepts. Therefore, commercial advertisements containing text and context of the local culture and contain sales messages to the audience.The data were analyzed with advertising discourse by utilizing several theories simultaneously. The theories will be used are the theory of discourse, pragmatic theory, and the theory of semiotics. The results of the research that has been done is as for the message is delivered in IKOMES more through nonverbal elements because more interesting. Nevertheless in advertising, to explain the nonverbal elements, at least one verbal element must be displayed, namely al-khaththur-raīsi or headline.